2019
DOI: 10.1021/acs.oprd.9b00403
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Gram-Scale Preparation of S-Trifluoromethyl Sulfoximines and Sulfilimino Iminiums, Powerful Reagents for the Late Stage Introduction of the CF3 Group

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The sulfoximine precursor 12 was synthesized on multigram scale from benzene ( 11 ), in 52 % yield over 4 steps according to our previous methodology (Scheme 2A, see Supporting Information for details) [21a,27] . Finally, ortho ‐iodination afforded racemic sulfoximine precursor 13 in 94 % yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfoximine precursor 12 was synthesized on multigram scale from benzene ( 11 ), in 52 % yield over 4 steps according to our previous methodology (Scheme 2A, see Supporting Information for details) [21a,27] . Finally, ortho ‐iodination afforded racemic sulfoximine precursor 13 in 94 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfoximine precursor 12 was synthesized on multigram scale from benzene ( 11 ), in 52 % yield over 4 steps according to our previous methodology (Scheme 2 A, see Supporting Information for details). [ 21a , 27 ] Finally, ortho ‐iodination afforded racemic sulfoximine precursor 13 in 94 % yield. Both enantiomers of the iodosulfoximine 13 could be separated by preparative chiral HPLC and were configurationally stable (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
“…The most illustrative examples of its importance include its use as a precursor of CF 3 À as demonstrated by Prakash et al, [3] or as a source of in situ generation of trifluoromethylcopper as shown by the group of Hu. [4] Another major application is the use of difluoro-and trifluoromethyl sulfoxides as common precursors of both sulfoniums [5] and sulfoximines, [6] two of the most widely used classes of electrophilic and radical di-or trifluoromethylation reagents. [7] Considering difluoromethyl sulfoxides, one of our groups (Leroux and coworkers) employed the enantiopure difluoromethanesulfinyl moiety as a chiral auxiliary to access highly enantioenriched α-difluoromethyl alcohols by deprotonation and trapping with electrophiles such as aldehydes or prochiral ketones.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the access to such α‐polyfluorinated alkyl aryl sulfoxides, Magnier and coworkers developed methods for either the direct introduction of the trifluoromethanesulfinyl group onto aryl derivatives, [5b,6a] or its construction via simple oxidation of the corresponding sulfides using TFPAA [12] . Unfortunately, all the attempts of asymmetric synthesis of aryl trifluoromethyl sulfoxides led to racemates [13] .…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are of great importance as ligands, auxiliaries, and catalysts, e.g., in asymmetric synthesis and catalysis. , Recently, a large number of reports on their synthesis and transformations have appeared in the literature, including halo- and chalcogenations. Sulfoximines undergo chlorinations with NCS (Figure a), brominations with NBS (Figure b), trifluoromethylthiolations with AgSCF 3 (Figure c), trifluoromethylations (Figure d), halocyclizations with (diacetoxyiodo)­benzene (DIB)/KI (Figure e), reactions with (DIB)/I 2 under visible light (Figure f), chlorinations and N -sulfonylations in the presence of I 2 /H 2 O 2 (Figure g), for example.…”
mentioning
confidence: 99%